MODELING THE DYNAMICS OF THE REFRACTION COEFFICIENT FIELD FOR RADIOWAVES OF THE CENTIMETER RANGE IN THE LOWER ATMOSPHERIC LAYER - Zinin D.P.; Teptin G.M.; Khutorova O.G.; Shlychkov A.P. (My University, 2007)
A mesoscale numerical model of the real nonstationary atmosphere (WRF with core ARW) was applied for the first time in this work to calculate spatiotemporal variations of 3D fields of the refraction coefficient for radiowaves of the centimeter range (hereafter, CR radiowaves) in the lower atmospheric layer on regional scales. A numerical analysis of the influence of spatial resolution of the model (from 1 to 10 km in the horizontal direction) on the quality of modeling showed that the high-resolution model appears more stable despite the significantly smaller area of the coverage on small time scales (high-quality modeling of the largest possible areas is significant due to the transport processes). This analysis was made on the basis of comparison with unique experimental data of long-term monitoring of atmospheric parameters with a time step of 1 min for different time scales, time of the year, and meteorological conditions. Such model is more preferable for modeling the refraction coefficient of the CR radiowaves. The calculations were performed for the territory of the Tatarstan republic. The deviation of the model from the experiment did not exceed 3–4% with respect to the root-mean-square scattering over the entire 10-yr period of observations, while the deviations do not exceed 20–40% in specific cases.